Gm6PGDH1, a Cytosolic 6-Phosphogluconate Dehydrogenase, Enhanced Tolerance to Phosphate Starvation by Improving Root System Development and Modifying the Antioxidant System in Soybean - Li, Cheng; Li, Kangning; Zheng, Mingming; Liu, Xinyi; Ding, Xianlong; Gai, Junyi; Yang, Shouping (Frontiers in Plant Science, 2021)
Phosphorus (P) plays an important role in plant growth and development, which is an important limiting factor for crop yield. Although previous studies showed that 6-phosphogluconate dehydrogenase (6PGDH) played an important role in plant resistance to adversity, its response to low P stress remained unknown. In this study, we reported the cloning and characterization of a cytosolic 6PGDH gene, Gm6PGDH1, which enhanced the tolerance to phosphate (Pi) starvation by improving root system development and modifying the antioxidant system in transgenic plants. Gm6PGDH1 was highly expressed in the root at full bloom stage, and strongly induced by Pi starvation. Results from intact soybean composite plant and soybean plant both containing Gm6PGDH1-overexpressing construct, showed that Gm6PGDH1 was involved in root system development, and subsequently affected P uptake under Pi-deficient condition. Meanwhile, the accumulation of reactive oxygen species (ROS) in the root tip of transgenic soybean was reduced and the activity of ROS-scavenging enzymes was enhanced compared with those of the wild type under Pi-deficient condition. Interestingly, we found that the overexpression of Gm6PGDH1 weakened the response of several other important Pi-answer genes to Pi starvation, such as some purple acid phosphatases and redox-related genes. In addition, the results from a virus-induced gene silencing indicated that Gm6PGDH1 might have functional redundancy in soybean. And the results from a heterogeneous transformation system showed that overexpressing Gm6PGDH1 also enhanced tolerance to Pi starvation in transgenic Arabidopsis. Together, these results suggested the great potential of Gm6PGDH1 in crop breeding for low Pi tolerance.